2012
DOI: 10.1684/pnv.2012.0351
|View full text |Cite
|
Sign up to set email alerts
|

Elders of 75 and over at an emergency service

Abstract: Les personnes âgées de 75 ans et plus en service d'urgencesElders of 75 and over at an emergency service Résumé. Contexte : Les personnes âgées représentent une part croissante de l'activité des services des urgences. Objectifs : Il s'agit de décrire la population de 75 ans et plus admise dans un service d'urgences et de comparer les patients adressés avec courrier de médecin à ceux sans. Méthodes : Une étude transversale, prospective, a été réalisée au Centre hospitalier de Mâcon, observant tous les patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…In our work, high blood pressure was the most common antecedent as well as in Hien et al in Burkina Faso [8]. Sough et al, in France found similar results [9]. Advancing age is believed to be associated with increased comorbidities and arterial hypertension remains the most frequent "silent killer" with high morbidity and mortality [10].…”
Section: Discussionsupporting
confidence: 81%
“…In our work, high blood pressure was the most common antecedent as well as in Hien et al in Burkina Faso [8]. Sough et al, in France found similar results [9]. Advancing age is believed to be associated with increased comorbidities and arterial hypertension remains the most frequent "silent killer" with high morbidity and mortality [10].…”
Section: Discussionsupporting
confidence: 81%
“…In 2007, individuals over 75 years old accounted for 8% of the population in France and according to the French National Institute for Statistics and Economic Studies, they will represent 16% of the population in 2040 . In the early 2000s, 12%–14% of all visits to emergency departments (ED) concerned patients over 75 years old . Fall‐related visits to the ED are very common among the elderly.…”
Section: Background and Importancementioning
confidence: 99%
“…Older patients represent up to 12%−24% of all emergency department (ED) visits (1)(2)(3)(4). The proportion of older people in society as well as in ED is constantly increasing (2, 3, 5-7).…”
Section: Introductionmentioning
confidence: 99%